Hemingway's genders : rereading the Hemingway text - Comley, Nancy R.; Scholes, Robert, 1929-2016. (New Haven : Yale University Press, 1994)
Ernest Hemingway has long been regarded as a fiercely heterosexual writer who advocated and embodied an exaggerated masculinity. This witty and intelligent book, the first to focus exclusively on gender in Hemingway's writing, presents a new view of the author, demonstrating that issues of gender and sexuality are more complex and subtle in his work than has ever been imagined.
Nancy R. Comley and Robert Scholes reread the Hemingway Text - his published and unpublished writing and what is known about his life - and show that gender was one of his conscious preoccupations. They explore the anguish and uncertainty beneath the blunt facade of Papa Hemingway; they examine a range of Hemingway's fictional women in such works as The Sun Also Rises and For whom the Bell Tolls and suggest that his best representations of women take on attributes of gender commonly viewed as male; they discuss how lesbianism, sex changes, and miscegenation appear in Hemingway's early and late writing; and they analyze examples of homosexual desire among boys and men in Hemingway's stories of bullfighters and soldiers.
1. Decoding Papa -- 2. Mothers, Nurses, Bitches, Girls, and Devils -- 3. Sea Changes and Tribal Things -- 4. Toros, Cojones, y Maricones.
Includes bibliographical references (pages 147-149) and index.
Print version record.
JSTOR
Keywords: Hemingway, Ernest, -- 1899-1961 -- Criticism and interpretation; Hemingway, Ernest, -- 1899-1961 -- Critique et interprétation.; Hemingway, Ernest, -- 1899-1961; Hemingway, Ernest -- 1899-1961; Hemingway, Ernest, -- (1899-1961) -- Critique et interprétation.; Hemingway, Ernest; Psychological fiction, American -- History and criticism; Masculinity in literature; Sex role in literature; Gender identity in literature; Masculinité dans la littérature.; Identité de genre dans la littérature.; Rôle selon le sexe dans la littérature.; LITERARY CRITICISM -- American -- General; Gender identity in literature; Masculinity in literature; Psychological fiction, American; Sex role in literature; Geschlechterrolle; Geschlechterrolle; Männlichkeit; Prosa; Roman; Sexualität; Sekseverschillen; Masculinité (psychologie) -- Dans la littérature.; Rôle selon le sexe -- Dans la littérature.; Identité (psychologie) -- Dans la littérature.; Criticism, interpretation, etc